A study on the fragmentation of saltating particles along the fetch distance during wind erosion - Avecilla, Fernando; Panebianco, Juan Esteban; Buschiazzo, Daniel Eduardo (Elsevier, 2018)
PM10 emission largely depends on the characteristics of the saltation process, which involves the movement of aggregate and isolated particles. Studies analyzing the relationship between the fragmentation of saltating aggregates and the dust emission along the fetch distance are very scarce. The objective of the present study was to analyze, on a loamy texture soil, the changes in the size distribution of the eroded sediment along the fetch distance under field conditions. Changes in the particle size distribution of the transported material were measured at four different heights above the soil surface every 25 m on a 200 m plot, during three strong wind erosion events. Statistically significant differences were found both for particle size distribution and aggregation when comparing the eroded sediment at the windward and leeward sides of the experimental plot. A greater proportion of coarser particles was found as the distance traveled by the eroded sediment increased. From the change in average particle size distribution at the beginning and at the end of the 200 m experimental plot, it was estimated that around 12% of the particles smaller than 62.5 μm were lost by vertical transport (dust plume) producing an average concentration of 48 µg m−3 at 2 m height and 200 m fetch. Under the conditions of this experiment, a soil aggregate transported by saltation was fragmented at a rate of 38% every 100 m traveled (R2 = 0.88; p < 0.001). Particle size analysis of the eroded sediment and open-air PM10 concentration measurements indicated that the fragmentation of aggregates during saltation can be considered as the main mechanism of dust emission on this soil.